Exploration of Klebsiella pneumoniae M6 for paclobutrazol degradation, plant growth attributes, and biocontrol action under subtropical ecosystem. - Govind Kumar; Shatrohan Lal; Shailendra K Maurya; A K Bhattacherjee; Parul Chaudhary; Saurabh Gangola; Shailendra Rajan (PLoS ONE)
In recent times, injudicious use of paclobutrazol (PBZ) in mango orchards deteriorates the soil quality and fertility by persistence nature and causes a serious ecosystem imbalance. In this study, a new Klebsiella pneumoniae strain M6 (MW228061) was isolated from mango rhizosphere and characterized as a potent plant growth promoter, biocontrol, and PBZ degrading agent. The strain M6 efficiently utilizes PBZ as carbon, energy and nitrogen source and degrades up to 98.28% (50 mgL-1 initial conc.) of PBZ at 15th day of incubation in MS medium. In the soil system first order degradation kinetics and linear model suggested 4.5 days was the theoretical half-life (t1/2 value) of PBZ with strain M6. Box Behnken design (BBD) model of Response surface methodology (RSM) showed pH 7.0, 31°C temperature, and 2.0 ml inoculum size (8 x 109 CFU mL-1) was optimized condition for maximum PBZ degradation with strain M6. Plant growth promoting attributes such as Zn, K, PO4 solubilization IAA, HCN and NH3 production of strain M6 showed positive results and were assessed quantitatively. The relation between plant growth promotion and PBZ degradation was analyzed by heat map, principal component analysis (PCA) and, clustal correlation analysis (CCA). Strain M6 was also showing a significant biocontrol activity against pathogenic fungi such as Fusarium oxysporum (MTCC-284), Colletotrichum gloeosporioides (MTCC- 2190), Pythium aphanidermatum (MTCC- 1024), Tropical race 1 (TR -1), and Tropical race 4 (TR -4). Hence, results of the study suggested that strain M6 can be utilized as an effective bio-agent to restore degraded land affected by persistent use of paclobutrazol.